A Case Study of Waste Bank Implementation in an Elementary School in Bonang Sub-District, Demak Regency - Marpaung, Sutan Sahala Muda; Kartika Ariswara; Yulizar Ihrami Rahmila; Varenna Faubiany; Mira Yulianti; Marwan Setiawan; Wawan Halwany; Bunga Resa Hartati; Hendris Syah Putra; Edgar Octoyuda (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: The community's behavior, perceptions, and willingness to pay (WTP) are vital in forming and implementing integrated waste management. Thus, zero waste theory advocates the need for research on perceptions, behavior, and WTP for school waste management. This study analyzes school residents' perceptions, behavior, and WTP regarding waste management. Methods: This study used a mixed-methods sequential explanatory design, combining quantitative and qualitative approaches. The study was conducted at SDN Betahwalang, selected purposively due to its active waste bank program. A total of 86 students and 75 school community members were surveyed. Quantitative data were analyzed using crosstabs and the Contingent Valuation Method (CVM), while qualitative data were obtained through in-depth interviews with key stakeholders. Results and Discussion: This study used a mixed-methods sequential explanatory design. The research was conducted at SDN Betahwalang, purposively selected for its active school waste bank program. The variables measured included students’ socio-economic characteristics, perception, environmental behavior, and willingness to pay for waste bank development. A total of 86 students and 75 school community members were surveyed. Data were analyzed using crosstabs and the Contingent Valuation Method, supported by qualitative insights from in-depth interviews. Conclusion: This study concludes that integrating environmental education through both formal and non-formal approaches effectively improves students’ knowledge, perception, and behavior toward waste management. Furthermore, the school community shows strong support for waste bank development, as indicated by their willingness to pay. These findings highlight the importance of institutional synergy and continuous environmental education in promoting sustainable waste practices in schools.